1991
DOI: 10.1007/bf00232617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of somaclonal variation during somatic embryogenesis of interior spruce (Picea glauca engelmannii complex) using culture morphology and isozyme analysis

Abstract: Somaclonal variation during interior spruce (Picea glauca engelmannii complex) somatic embryogenesis was evaluated using culture morphology and isozyme analysis. Genotype-specific abscisic acid-dependent developmental profiles and isozyme patterns were similar for subclone and parent line embryogenic cultures and cotyledonary somatic embryos. Extensive analysis of fifteen hundred subclone embryos of one genotype revealed no isozyme pattern variation. Initiation of embryogenic cultures was dependent on the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…On the other hand POD pattern of the V133 was most polymorphic. The dissociation of the POD and EST isoforms and induction of new forms was related to somaclonal variation in in vitro plants in other species as well (9)(10)(11). All isoform of the acid phosphatase were very intensive unlike previous report previously (7) and highly polymorphic regardless of the clone origin.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand POD pattern of the V133 was most polymorphic. The dissociation of the POD and EST isoforms and induction of new forms was related to somaclonal variation in in vitro plants in other species as well (9)(10)(11). All isoform of the acid phosphatase were very intensive unlike previous report previously (7) and highly polymorphic regardless of the clone origin.…”
Section: Discussionmentioning
confidence: 66%
“…Recent molecular studies on genetic stability of black spruce embryogenic cultures showed no variation within the clones (Isabel et al, 1993). The basis for the apparent genetic stability of these embryogenic cultures is unknown but may be related to their embryogenic character (Eastman et a!., 1991 In herbaceous plants, however, the occurrence of…”
Section: Resultsmentioning
confidence: 99%
“…These methods are considered to produce genetically uniform and true-to-type plants, because the organised meristems generally are believed to be immune to genetic changes [28,29]. Several reports of experimental studies support this view [30,31,32,33,34,35]. However, there is an increasing body of evidence that indicates that in embryogenic cultures, selection in favour of 'normal cells' does not always take place during development and that growth of mutant cells can occur as well, which can induce variability in the cultures [36].…”
Section: Regeneration Systemsmentioning
confidence: 99%
“…Cytometry has been used to identify the particular characteristics of somaclonal variation in Vitis vinifera [83,84,85] and Citrus lemon [7]. Proteins and isozymes have been used widely as markers for identifying cultivars and characterising somaclonal variation in many fruit species [33]. Isozyme analysis has been used to assess genetic fidelity in Citrus plants regenerated through organogenesis, and somatic embryogenesis [86].…”
Section: Morphological Cytological and Biochemical Markersmentioning
confidence: 99%